Heavy $$K^*$$ K ∗ mesons with open charm from $$KD^{(*)}D^*$$ K D ( ∗ ) D ∗ interactions - Xiu-Lei Ren; K. P. Khemchandani; A. Martínez Torres (European Physical Journal C: Particles and Fields, 2024)
Abstract In view of the recent discovery of $$T_{cc}$$ T cc , which can be described as a $$DD^*$$ D D ∗ molecular state, we perform a study of the $$KDD^*$$ K D D ∗ system, and its extension to studying $$KD^*D^*$$ K D ∗ D ∗ , where $$D^*D^*$$ D ∗ D ∗ is bound as a spin 1 $$T_{cc}$$ T cc -like state, to search for the possible existence of exotic mesons with the open flavors ccs being part of their quark configuration. Considering the additional attractive interactions present in the KD and $$KD^*$$ K D ∗ subsystems, where the states $$D^*_{s0}(2317)$$ D s 0 ∗ ( 2317 ) and $$D_{s1}(2460)$$ D s 1 ( 2460 ) are generated, we solve the Faddeev equations considering the fixed-center approximation for the mentioned three-body systems and find the existence of two doubly charmed $$K^*$$ K ∗ -like mesons, $$K_{cc}^*(4309)$$ K cc ∗ ( 4309 ) and $$K_{cc}^*(4449)$$ K cc ∗ ( 4449 ) , with quantum numbers $$I(J^P)=1/2\,(1^-)$$ I ( J P ) = 1 / 2 ( 1 - ) . Considering the respective three-body thresholds of the two systems, both $$K_{cc}$$ K cc -states are bound by around 60 MeV. An experimental confirmation will bring evidence for the existence of a degree of exoticity beyond charm +2.